Polybrominated diphenyl ethers in thirteen shark species from offshore and coastal waters of Korea. Issue 1 (15th June 2015) - Lee, Hyun-Kyung; Kim, Sang-Jo; Jeong, Yunsun; Lee, Sunggyu; Jeong, Woochang; Lee, Won-Chan; Choy, Eun-Jung; Kang, Chang-Keun; Moon, Hyo-Bang
Highlights: PBDEs were measured in muscles from 105 individuals of 13 shark species. Inter- and intra-species differences in sharks were found for PBDE accumulation. Highest levels of PBDEs were found for aggressive carnivore sharks. Diet, growth, and local contamination were major contributors for PBDE accumulation. Abstract: Limited reports are available on polybrominated diphenyl ethers (PBDEs) in sharks. In this study, PBDEs were measured in dorsal muscles ( n  = 105) from 13 shark species collected from offshore and coastal waters of Korea. The PBDE concentrations varied greatly not only among species but also within species of sharks. The major PBDE congeners detected in our samples were BDEs 47, 28, 99, 153, 100, and 154. Concentrations of PBDEs in sharks in this study were lower than those reported for previous studies. The high PBDE concentrations were found for aggressive shark species. Inter-species differences in the concentrations and accumulation profiles of PBDEs are explained by differences in feeding habits and sampling locations. Several contributing factors such as growth velocity, trophic level, and local contamination may affect the bioaccumulation of PBDEs in sharks. The present study provides baselines for the occurrence and accumulation status of PBDEs in various shark species.